Impact of perinatal depressive and anxiety symptoms and infant temperament on exclusive breastfeeding: a cohort study in Malaysia - Nasreen, Hashima E; Ab Rahman, Jamalludin; Pasi, Hafizah; Md Aris, Mohd Aznan; Mohd Rus, Razman; Edhborg, Maigun (2023)
Purpose: The purpose of the study was to examine the impact of perinatal depressive and anxiety symptoms and infant temperament at 6 months postpartum on exclusive breastfeeding, and whether maternal depressive and anxiety symptoms at 6 months postpartum are moderators on the association between infant temperament and exclusive breastfeeding. Methods: We used data from a perinatal mental health cohort study conducted in health clinics in two states of Malaysia. Edinburgh Postnatal Depression Scale (EPDS) and anxiety subscale of Depression, Anxiety and Stress Scale (DASS) were completed by 524 parents at late pregnancy and 6 months postpartum, while the Infant Characteristic Questionnaire and information on exclusive breastfeeding were completed by 524 mothers at 6 months postpartum. Results: Mothers’ postpartum depressive symptoms (PDS) at 6 months were associated with shorter duration of exclusive breastfeeding, but not the postpartum anxiety symptoms (PAS). Mothers with persistent depressive and anxiety symptoms ceased exclusive breastfeeding earliest. Mothers’ perceptions of infant temperament and its subscales were negatively associated with exclusive breastfeeding duration only in depressed mothers, but not in non-depressed, anxious, and non-anxious mothers. Therefore, mothers’ PDS, not PAS, moderated the association between mothers’ perceptions of infant temperament and the duration of exclusive breastfeeding. Conclusion: The results signify the need to address maternal mental health in early postpartum and healthcare professionals should consider the role of maternal depression when working with mothers who report their infants as temperamentally challenging.